Increasing Village Community Knowledge Through Socialization of the waste Independent Village Program - Titin, Titin; Tonce, Yosef; S, Siktania Maria Dilliana; Tanur, Evelin Anggelina; Winarti, Thresia; Hamidah, Emmy (Universitas Pahlawan Tuanku Tambusai, 2024)
Increasing population growth in an area is accompanied by an increase in the volume of waste produced. Waste is an item resulting from human activities and other living creatures that is no longer used. The waste produced in an area is basically determined by the activities of the people in that place. These activities include trade, housing, office, industrial, agricultural and other activities. An increase in waste volume that is not balanced by an integrated waste management system can cause problems in an area. The waste problem also occurs in Karangturi Village, Glagah District, Lamongan Regency, East Java. Referring to the conditions in Karangturi Village, Glagah District, where there is still a waste problem, Community Service activities are being carried out to increase the community's ability to manage waste independently. To overcome this problem, one alternative solution that can be implemented is by holding an independent waste village program to manage the use of household waste in realizing independent and sustainable development in Karangturi Village, Glagah District, Lamongan Regency, East Java. Therefore, the aim of this community service is to see the potential for increasing village community knowledge through the socialization of the Independent Waste Village Program in Karangturi Village, Glagah District, Lamongan Regency, East Java. To obtain the data used were observation and literature review. As a form of the author's thinking, several efforts and breakthroughs are offered, namely: 1.) Increasing the knowledge of the community who already know that household waste can be utilized so as to create community welfare, 2.) The role of utilizing household waste for the Karangturi Village community in realizing sustainable village development is to improve the quality of life to be cleaner and healthier.